Bi-Parabolic Graded Buffer Layers for Metamorphic Devices. (25th October 2017) - Song, Yifei; Kujofsa, Tedi; Ayers, John E
Abstract : Metamorphic semiconductor devices such as high electron mobility transistors (HEMTs), light-emitting diodes (LEDs), laser diodes, and solar cells are grown on mismatched substrates and typically exhibit a high degree of lattice relaxation. Linearly-graded buffer layers are commonly used to accommodate the lattice mismatch in these structures, but theoretical and experimental studies suggest that non-linear compositional grading might allow lower threading dislocation densities and improved device performance. In this work we have compared the threading dislocation densities in heterostructures employing bi-parabolic, linear, and S-graded (complementary error function) buffer layers. The threading dislocation densities were calculated using the approximate Matthews, Mader, and Light model (1) for plastic flow and by assuming that the coefficient for second-order annihilation and coalescence reactions between threading dislocations is equal to the length of misfit dislocations.